miR-106a* inhibits the proliferation of esophageal carcinoma cells by targeting CDK2-associated Cullin 1 (CACUL1) - Ma, H L; Wen, X P; Zhang, X Z; Wang, X L; Zhao, D L; Che, S M; Dang, C X (Cellular and Molecular Biology, 2015)
Previous studies suggest that aberrant microRNA expression is common in plenty of cancers. The expression of miR-106a* was decreased in follicular lymphoma, but the expression and functions of miR-106a* in esophageal carcinoma (EC) remain unclear. In this study, we explored the expression and anti-oncogenic roles of miR-106a* in human EC. The expression of miR-106a* is significantly decreased in EC tissues and EC cell lines. Overexpression of miR-106a* suppressed EC cell proliferation, clonogenicity, G1/S transition, and induced apoptosis in vitro, but inhibition of miR-106a* facilitated cell proliferation, clonogenicity, G1/S transition. Luciferase reporter assay results showed that CDK2-associated Cullin 1 (CACUL1) was a direct target of miR-106a* in EC cells. Moreover, silencing CACUL1 resulted in the same biologic effects of miR-106a* overexpression in EC cells, which included suppressed EC cell proliferation, clonogenicity, and blocked G1/S transition through CDK2 pathway by inhibiting cell cycle regulators (Cyclin A, Cyclin E). Our data indicate that miR-106a* might play an anti-oncogenic role in EC by regulating CACUL1 expression, which suggest miR-106a* as a new potential diagnostic and therapeutic target for EC.